Pathogenic Factors of Shiga Toxigenic Escherichia coli - Tharakupeedikayil Abdul Majeed Sajeena; Sudha Kalyanikutty (Journal of Pure and Applied Microbiology, 2024)
The Shigatoxigenic Escherichia coli (STEC) are bacterial enteropathogens responsible for some intensive clinical syndromes such as bloody diarrhoea, hemorrhagic colitis, hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, and renal failure. These pathotypes come under the Enterohemorrhagic Escherichia coli (EHEC) group. Monogastric farm animals such as pigs, horses, chickens, ducks, turkeys and aquatic animals like shellfish, fishes, and wild animals can act as major spillover hosts of STEC strains and could serve as the potential source of infection. The pathogen is notorious as a quickly emergent strain with acquired characteristics like different variants of Shigatoxin, many antibiotic degrading enzymes, Intimin, Enterohemolysin, Auto-agglutination Adhesins, Catalase-peroxidase, Zinc metalloprotease, Subtilase cytotoxin, tolerance to multiple adverse conditions, and biofilm formation. The bacteria are known for its long survival in different adverse physical-chemical conditions. The formation of biofilm is one of the major factors responsible for their persistence. Multidrug resistance is another related trait contributing to the high mortality rate of these strains. STEC strains are good candidates for studying the emergence of pathogens with acquired characteristics like genes. In this article, various virulent traits and multidrug resistance that enabled the strain to emerge as a serious public health menace were reviewed.